Method for manufacturing a connection structure and a connection film
Patent Information
- Application Number
- CN202280032712.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-12
- Filing Date
- 2022-04-28
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-04-28
Smart Images

Figure CN117280450B_ABST
Abstract
Description
Technical Field
[0001] This technology relates to a method for manufacturing a connection structure for connecting chip components to a substrate, and a connection film. This application claims priority based on Japanese Patent Application No. 2021-081171, filed on May 12, 2021, which is incorporated herein by reference. Background Technology
[0002] In recent years, the development of micro-LEDs, as the next generation of displays after LCD (Liquid Crystal Display) and OLED (Organic Light Emitting Diode), has been very active. As a research topic related to micro-LEDs, a technique called mass transfer, which involves mounting micrometer-sized LEDs onto a panel substrate, is being studied in various locations.
[0003] As the primary method of mass transfer, there is a method that uses molding materials to transfer LEDs to the panel substrate side. Figure 11 This is a schematic diagram illustrating the quality transfer in an imprinting method. In an imprinting method, such as... Figure 11 (A) and Figure 11 As shown in (B), LED 101 is transferred from transfer material 102 to impression material 103 and then picked up, as follows. Figure 11 (C) and Figure 11 As shown in (D), LED 101 is attached to the connecting film 105 of panel substrate 104. However, in the method using imprinting material, the spacing of LED 101 depends on the pattern of imprinting material 103, resulting in low design freedom, low chip transfer rate, and is very time-consuming, making it unsuitable for mass production.
[0004] Therefore, the chip configuration method using lasers is now attracting attention (see, for example, patent documents 1 to 4). Figure 12 This is a schematic diagram illustrating mass transfer in a laser-based manner. In the laser-based process, such as... Figure 12 (A) and Figure 12 As shown in (B), LED 111 is transferred from transfer material 112 to release material 113 and picked up, as follows: Figure 12 As shown in (C), a laser is irradiated onto the release material 113, causing the LED 111 to land on the connecting film 115 of the panel substrate 114. Compared with molded materials, laser-based chip transfer offers greater design freedom and a much faster chip transfer cycle.
[0005] However, in chip configuration methods that utilize lasers, the LEDs are bounced up and fall onto the panel substrate at a very high speed, thus, for example... Figure 12As shown in (D), LED misalignment, deformation, detachment, or damage can cause adverse effects.
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-096144
[0009] Patent Document 2: Japanese Patent Application Publication No. 2020-145243
[0010] Patent Document 3: Japanese Patent Application Publication No. 2019-176154
[0011] Patent Document 4: Japanese Patent Application Publication No. 2020-053558 Summary of the Invention
[0012] The problem that the invention aims to solve
[0013] This technology is a solution proposed in view of the past situation, providing a method for manufacturing a connecting structure and a connecting film that can achieve excellent adhesion and conductivity of chip components based on laser irradiation.
[0014] Solution for solving the problem
[0015] The manufacturing method of the connection structure of this technology includes: a landing step in which a chip component disposed on a substrate material that is permeable to laser light is placed opposite a wiring substrate, and the chip component is irradiated with laser light from the substrate material side to land on the wiring substrate side; and a connection step in which the chip component and the wiring substrate are connected via a connection film, the connection film having a rubber layer and an adhesive layer. In the landing step, the connection film is disposed on the electrode surface of the wiring substrate, and the rubber layer collides with the electrode surface of the chip component.
[0016] The manufacturing method of the connection structure of this technology includes: a landing step in which a chip component disposed on a substrate material that is permeable to laser light is placed opposite a wiring substrate, and the chip component is irradiated with laser light from the substrate material side to land on the wiring substrate side; and a connection step in which the chip component and the wiring substrate are connected via a connection film, wherein the connection film has an adhesive layer and the chip component has a rubber layer on an electrode surface. In the landing step, the connection film is disposed on the electrode surface of the wiring substrate, and the adhesive layer collides with the rubber layer of the chip component.
[0017] The manufacturing method of the connection structure of this technology includes: a landing step in which a chip component disposed on a substrate material that is permeable to laser light is placed opposite a wiring substrate, and a laser is irradiated from the substrate material side to cause the chip component to land on the wiring substrate side; and a connection step in which the chip component and the wiring substrate are connected via a connection film, the connection film having a rubber layer and an adhesive layer. In the landing step, the connection film is disposed on the electrode surface of the chip component, and the rubber layer collides with the electrode surface of the wiring substrate.
[0018] The manufacturing method of the connection structure of this technology includes: a landing step in which a chip component disposed on a substrate material that is permeable to laser light is placed opposite a wiring substrate, and a laser is irradiated from the substrate material side to cause the chip component to land on the wiring substrate side; and a connection step in which the chip component and the wiring substrate are connected via a connection film, wherein the connection film has an adhesive layer and the wiring substrate has a rubber layer on an electrode surface. In the landing step, the connection film is disposed on the electrode surface of the chip component, and the adhesive layer collides with the rubber layer of the wiring substrate.
[0019] The connecting film of this technology has a rubber layer and an adhesive layer, wherein the thickness of the rubber layer is more than 0.5 μm and less than 3.0 μm.
[0020] Invention effect
[0021] According to this technology, due to the excellent shock absorption, the chip components can achieve excellent landing properties and excellent conductivity. Attached Figure Description
[0022] Figure 1 It is a schematic cross-sectional view showing the state in which the light-emitting element disposed on the substrate material is facing the connecting film on the wiring board.
[0023] Figure 2 This is an enlarged view showing the connection film between the opposing light-emitting element and the wiring substrate.
[0024] Figure 3 It is a cross-sectional view schematically showing the state in which a laser is irradiated from the substrate side, causing the light-emitting elements to be transferred and arranged in a predetermined position on the wiring substrate.
[0025] Figure 4 It is a schematic cross-sectional view showing the state in which the light-emitting element is mounted on the wiring board.
[0026] Figure 5 It is a schematic cross-sectional view showing a light-emitting element disposed on a substrate material and having a rubber layer on the electrode surface facing an anisotropic conductive adhesive layer on a wiring substrate.
[0027] Figure 6 It is a schematic cross-sectional view showing a light-emitting element disposed on a substrate material and having a connecting thin film on the electrode surface facing a wiring substrate.
[0028] Figure 7 It is a schematic cross-sectional view showing a light-emitting element disposed on a substrate material and having an anisotropic conductive adhesive layer on the electrode surface facing a rubber layer on a wiring substrate.
[0029] Figure 8 This is a cross-sectional view schematically showing a first example of the structure of the connecting film.
[0030] Figure 9 (A) is a top view showing two rubber layers with internal gaps created through processing. Figure 9 (B) is a cross-sectional view schematically showing a second example of the connecting film.
[0031] Figure 10 This is a schematic cross-sectional view illustrating a third example of the connecting film.
[0032] Figure 11 It is a diagram that schematically represents the quality transfer of the imprinting method.
[0033] Figure 12 This is a schematic diagram illustrating mass transfer via laser. Detailed Implementation
[0034] Hereinafter, embodiments of the present technology will be described in detail with reference to the accompanying drawings in the following order.
[0035] 1. Manufacturing method of connecting structures
[0036] 2. Connecting the film
[0037] 3. Example
[0038] <1. Manufacturing method of connecting structures>
[0039] [First Implementation Method]
[0040] The manufacturing method of the connection structure according to the first embodiment includes: a landing step in which a chip component disposed on a substrate material that is permeable to laser light is placed opposite a wiring substrate, and a laser is irradiated from the substrate material side to cause the chip component to land on the wiring substrate side; and a connection step in which the chip component and the wiring substrate are connected via a connection film, the connection film having a rubber layer and an adhesive layer. In the landing step, the connection film is disposed on the electrode surface of the wiring substrate, and the rubber layer collides with the electrode surface of the chip component. As a result, in the landing step, defects such as chip component misalignment, deformation, damage, and detachment are suppressed, and the chip component can be transferred and arranged with high precision and high efficiency. In the connection step, the chip component penetrates the rubber layer, and excellent conductivity is obtained, thus reducing the cycle time.
[0041] The adhesive layer in the bonding film is preferably an anisotropic conductive adhesive layer containing conductive particles. This allows the chip component to be connected to the wiring substrate even when the chip component does not have connection points such as eutectic solder bumps. Furthermore, even if the electrodes of the chip component are protruding, and electrical wiring connection with the wiring substrate is achieved, the adhesive layer may not contain conductive particles.
[0042] Examples of chip components include semiconductor chips and LED chips, without particular limitation. However, the manufacturing method of the connection structure of this technology is suitable for mass transfer of mounting a large number of micron-sized LED chips onto a panel substrate that serves as a wiring substrate.
[0043] The following describes a method for manufacturing a display device in which multiple light-emitting elements, which are LED chips, are arranged on a wiring board, which is a panel substrate, to form a light-emitting element array.
[0044] As a light-emitting element, it can be used in so-called flip-chip LEDs, which have a first conductive electrode and a second conductive electrode on one side. The light-emitting elements are arranged on the substrate in correspondence with the sub-pixels that constitute a pixel, forming a light-emitting element array. A pixel may be composed of three sub-pixels: R (red), G (green), and B (blue); or it may be composed of four sub-pixels: RGBW (white) and RGBY (yellow); or it may be composed of two sub-pixels: RG and GB.
[0045] As for subpixel arrangement methods, for example in the RGB case, examples include striped arrangement, tessellated arrangement, and triangular arrangement. Striped arrangement arranges RGB pixels into vertical stripes, achieving high resolution. Tessellated arrangement, on the other hand, tilts the same color of RGB pixels, resulting in a natural image. Triangular arrangement, arranging RGB pixels into triangles with each point offset by half a spacing per field, also produces a natural image display.
[0046] Table 1 shows the estimated horizontal spacing between RGB chips, estimated chip size, and estimated electrode size for PPI (Pixels Per Inch) when the RGB chips are arranged horizontally. The minimum chip spacing is assumed to be 5 μm, and the estimated maximum spacing between RGB chips is when they are evenly spaced. These values were calculated as reference values for clarifying applications and studying this technology.
[0047] [Table 1]
[0048]
[0049] As shown in Table 1, a chip size of 10×20μm corresponds to a PPI of 500. Furthermore, a chip size of 7×14μm corresponds to a PPI of 1000, and by further reducing the chip size, a PPI exceeding 1000 can be achieved. Moreover, the chip does not necessarily have to be rectangular; it can also be square.
[0050] The following is for reference Figures 1-4 The landing process (A1) in which the light-emitting element is placed on the wiring board side by irradiating with a laser, and the connection process (B1) in which the light-emitting element is connected to the wiring board are described.
[0051] [Landing process (A1)]
[0052] Figure 1 It is a schematic cross-sectional view showing the state in which the light-emitting element disposed on the substrate material and the connecting film on the wiring board are facing each other. Figure 2 This is an enlarged view showing the connection film between the opposing light-emitting element and the wiring substrate. For example... Figure 1 as well as Figure 2 As shown, firstly, in the placement process (A1), the chip component substrate 10 is positioned opposite the wiring substrate 30.
[0053] The chip component substrate 10 includes a substrate material 11, a release material 12, and a light-emitting element 20, with the light-emitting element 20 attached to the surface of the release material 12. The substrate material 11 only needs to be translucent to the laser, and is preferably quartz glass with high transmittance throughout the entire wavelength.
[0054] The release material 12 only needs to have absorption characteristics relative to the wavelength of the laser. The laser irradiation generates a shock wave, which propels the light-emitting element 20 toward the wiring substrate 30. Polyimide can be used as an example of the release material 12. The thickness T12 of the release material 12 is, for example, 0.5 μm or more.
[0055] The light-emitting element 20 includes a body 21, a first conductive electrode 22, and a second conductive electrode 23. The first conductive electrode 22 and the second conductive electrode 23 have a horizontal configuration arranged on the same side. The body 21 has a so-called dual heterostructure, which includes, for example, a first conductive coating layer made of n-GaN, and, for example, an In... x Al y Ga 1-x-y The active layer consists of an N-layer and a second conductive coating layer, for example, composed of p-GaN. A first conductive electrode 22 is formed on a portion of the first conductive coating layer through a passivation layer, and a second conductive electrode 23 is formed on a portion of the second conductive coating layer. When a voltage is applied between the first conductive electrode 22 and the second conductive electrode 23, the carrier concentrates in the active layer, and light emission is generated through recombination.
[0056] The width W20 of the light-emitting element 20 is, for example, 1 to 100 μm, and the thickness T20 of the light-emitting element 20 is, for example, 1 to 20 μm.
[0057] The wiring substrate 30 has a first conductivity type circuit pattern and a second conductivity type circuit pattern on the substrate material 31. For example, a first electrode 32 and a second electrode 33 are respectively provided at positions corresponding to the first conductivity type electrode on the p side and the second conductivity type electrode on the n side, so that the light-emitting elements are arranged in sub-pixel units constituting one pixel. In addition, the wiring substrate 30 forms circuit patterns such as data lines and address lines of matrix wiring, which can connect and disconnect the light-emitting elements corresponding to each sub-pixel constituting one pixel. Furthermore, the wiring substrate 30 is preferably a light-transmitting substrate, the substrate material 31 is preferably a transparent substrate material such as glass, PET (Polyethylene Terephthalate), or polyimide, and the circuit pattern, the first electrode 32, and the second electrode 33 are preferably transparent conductive films such as ITO (Indium-Tin-Oxide), IZO (Indium-Zinc-Oxide), ZnO (Zinc-Oxide), or IGZO (Indium-Gallium-Zinc-Oxide).
[0058] As described below, the connecting film 40 has a rubber layer 41 and an anisotropic conductive adhesive layer 42, and is adhered to the wiring substrate 30 with the rubber layer 41 side facing the light-emitting element 20. The rubber layer 41 is preferably one or more selected from silicone rubber and acrylic rubber. The thickness of the rubber layer 41 is preferably 0.5 μm or more and 3.0 μm or less, more preferably 0.5 μm or more and 2.0 μm or less, and even more preferably 0.5 μm or more and 1.5 μm or less. Furthermore, the rubber layer 41 preferably has internal voids and is preferably in a mesh-like, protruding, or similar shape. This improves cushioning during the landing process and enhances the transmittance of the light-emitting element 20 during the connection process. The anisotropic conductive adhesive layer 42 preferably contains conductive particles 43 in a thermosetting adhesive.
[0059] The thickness T40 of the connecting film 40 is, for example, 20 μm or less. In addition, the distance D between the light-emitting element 20 and the connecting film 40 is preferably 10 to 1000 μm, more preferably 50 to 500 μm, and even more preferably 80 to 200 μm.
[0060] Figure 3 This is a schematic cross-sectional view illustrating the state in which a laser beam is irradiated from the substrate side, causing the light-emitting elements to be transferred and arranged at predetermined positions on the wiring substrate. For example... Figure 2 as well as Figure 3 As shown, in the landing process (A1), laser 50 is irradiated from the substrate 11 side, causing the light-emitting element 20 to be transferred to a predetermined position on the wiring substrate 21 and arranged on the connecting film 40.
[0061] The transfer of the light-emitting element 20 can be achieved, for example, using a laser-induced forward transfer (LIFT) device. The device includes, for example, a telescoping member that parallelizes a pulsed laser emitted from a laser device; a shaping optical system that uniformly shapes the spatial intensity distribution of the pulsed laser after passing through the telescoping member; a mask that allows the pulsed laser shaped by the shaping optical system to pass through in a predetermined pattern; a field lens located between the shaping optical system and the mask; and a projection lens that reduces the projection of the laser patterned through the mask onto a donor substrate. The chip component substrate 10, serving as the donor substrate, is held on a donor stage, and the wiring substrate 30, serving as the recipient substrate, is held on a recipient stage.
[0062] As a laser device, for example, an excimer laser that oscillates with a wavelength of 180 nm to 360 nm can be used. The oscillation wavelength of the excimer laser is, for example, 193, 248, 308, or 351 nm, and can be appropriately selected from the above-mentioned oscillation wavelengths according to the light absorption properties of the material 12.
[0063] The mask uses a pattern of windows of a predetermined size arranged at predetermined intervals so that the projection in the boundary between the substrate material 11 and the release material 12 is the desired laser arrangement. In the mask, for example, a pattern is applied to the substrate material 11 by chrome plating, the unplated window portions allow the laser to pass through, and the chrome-plated portions block the laser.
[0064] The emitted light from the laser device enters the telescopic optical system and propagates into the previous shaping optical system. The laser light that has just entered the shaping optical system is also adjusted by the telescopic optical system to be approximately parallel light at any position within the X-axis movement range of the donor stage, so it always enters relative to the shaping optical system at approximately the same size and angle (perpendicular).
[0065] After passing through the shaping optical system, the laser beam, in combination with the projection lens, passes through the field lens constituting the image-side focal stop reduction projection optical system and enters the mask. After passing through the mask pattern, the laser beam's propagation direction is changed to vertical downward by the incident mirror and enters the projection lens. The laser beam emitted from the projection lens enters from the side of the substrate material 11 and is accurately projected at a predetermined position on the release material 12 formed on its surface (lower surface) at a reduced size of the mask pattern.
[0066] The pulse energy of the imaging laser irradiating the interface between the substrate material 11 and the release material 12 is preferably 0.001 to 2 J, more preferably 0.01 to 1.5 J, and even more preferably 0.1 to 1 J. The flow rate is preferably 0.001 to 2 J / cm³. 2 More preferably, it is 0.01 to 1 J / cm³. 2 More preferably, it is 0.05–0.5 J / cm. 2 The pulse width (irradiation time) is preferably 0.01 to 1×10⁻⁶. 9 picoseconds. More preferably 0.1 to 1 × 10⁻⁶. 7 picosecond, further preferably 1 to 1×10 5 The pulse frequency is preferably 0.1 to 10000 Hz, more preferably 1 to 1000 Hz, and even more preferably 1 to 100 Hz. The number of irradiation pulses is preferably 1 to 30,000,000.
[0067] By using this lifting device, at the interface between the substrate material 11 and the release material 12, the release material 12, which has been irradiated with laser, generates a shock wave, causing multiple light-emitting elements 20 to be peeled off from the substrate material 11 and lifted toward the wiring substrate 30. This allows multiple light-emitting elements 20 to be placed at predetermined positions on the wiring substrate 30 via the connecting film 40.
[0068] The connecting film 40 has a rubber layer 41 on the side of the multiple light-emitting elements 20, which can mitigate the impact when the light-emitting elements 20, which are ejected at ultra-high speed, land, suppress the occurrence of defects such as displacement, deformation, damage, and detachment of the light-emitting elements 20, and achieve a high landing success rate.
[0069] [Connection Process (B1)]
[0070] Figure 4 This is a schematic cross-sectional view showing the state in which the light-emitting element is mounted on the wiring board. For example... Figure 4 As shown, in the connection process (B1), light-emitting elements 20 are installed and arranged at predetermined positions on the wiring board 30.
[0071] As a method for hot-pressing the light-emitting element 20 onto the wiring substrate 30, a connection method used in known anisotropic conductive films can be appropriately selected and used. For example, the hot-pressing conditions are a temperature of 150°C to 260°C, a pressure of 5 MPa to 60 MPa, and a time of 5 seconds to 300 seconds.
[0072] During thermoforming, the rubber layer 41 connecting the thin film 40 is penetrated by the first conductive electrode 22 and the second conductive electrode 23 of the light-emitting element 20. Furthermore, the conductive particles 43 of the anisotropic conductive adhesive layer 42 are sandwiched between the first conductive electrode 22 and the second conductive electrode 23 of the light-emitting element 20 and the first electrode 32 and the second electrode 33 of the wiring substrate 30, and cured by the adhesive of the anisotropic conductive adhesive layer 42, thereby forming an anisotropic conductive film.
[0073] According to the manufacturing method of the connection structure according to the first embodiment, by disposing a connection film having a rubber layer and an adhesive layer on the electrode surface of the wiring substrate and colliding the rubber layer with the electrode surface of the chip component, the chip component can be suppressed from misalignment, deformation, damage, detachment and other defects during the landing process, so that the chip component can be transferred and arranged with high precision and high efficiency. During the connection process, the chip component can penetrate the rubber layer and obtain excellent conductivity.
[0074] In the first embodiment, the bonding film is adhered to the entire surface of the wiring substrate. However, for example, mass transfer technology can be used to transfer individual pieces of the bonding film to the electrode positions on the wiring substrate. By selectively adhering the bonding film only at the locations where chip components pop out, rather than adhering the entire surface, the transparency of the light-emitting element array can be improved, for example.
[0075] [Second Implementation]
[0076] In the first embodiment, a connecting film having a rubber layer and an adhesive layer is disposed on a wiring substrate, but the rubber layer may also be disposed on the electrode surface of the chip component and the adhesive layer may be disposed on the wiring substrate.
[0077] That is, the manufacturing method of the connection structure in the second embodiment includes: a landing step in which a chip component disposed on a substrate material that is permeable to laser light is placed opposite a wiring substrate, and a laser light is irradiated from the substrate material side to cause the chip component to land on the wiring substrate side; and a connection step in which the chip component and the wiring substrate are connected via a connection film, the connection film having an adhesive layer, the chip component having a rubber layer on an electrode surface, and in the landing step, the connection film is disposed on the electrode surface of the wiring substrate, and the adhesive layer collides with the rubber layer of the chip component.
[0078] Hereinafter, similar to the first embodiment, the method for manufacturing a display device in which multiple light-emitting elements, which are LED chips, are arranged on a wiring substrate, which is a panel substrate, to form a light-emitting element array, will be described as a method for manufacturing a connection structure. Furthermore, structures identical to those in the first embodiment will be labeled with the same reference numerals and their descriptions will be omitted.
[0079] [Landing process (A2)]
[0080] Figure 5 This is a schematic cross-sectional view showing a light-emitting element disposed on a substrate material and having a rubber layer on the electrode surface facing an anisotropic conductive adhesive layer on a wiring substrate. For example... Figure 5 As shown, firstly, in the placement process (A2), the chip component substrate 10 is positioned opposite the wiring substrate 30.
[0081] The chip component substrate 10 includes a substrate material 11, a release material 12, and a light-emitting element 20, with the light-emitting element 20 attached to the surface of the release material 12. Additionally, a rubber layer 51 is attached to the electrode surface of the light-emitting element 20. The rubber layer 51 is the same as the rubber layer 41 in the first embodiment, and therefore its description is omitted.
[0082] The connecting film 50 is composed of an anisotropic conductive adhesive layer 52 and is attached to the first electrode 32 and the second electrode 33 of the wiring substrate 30. The anisotropic conductive adhesive layer 22 is the same as the anisotropic conductive adhesive layer 42 in the first embodiment, so its description is omitted.
[0083] In the landing process (A2), the rubber layer 51 attached to the light-emitting element 20 mitigates the impact when the light-emitting element 20, which is ejected at ultra-high speed, lands on the anisotropic conductive adhesive layer 52, suppressing the occurrence of defects such as displacement, deformation, damage, and detachment of the light-emitting element 20, and thus achieving a high landing success rate.
[0084] [Connection process (B2)]
[0085] In the connection process (B2), the arranged light-emitting elements 20 are mounted at predetermined positions on the wiring substrate 30. The method of heat-pressing the light-emitting elements 20 onto the wiring substrate 30 is the same as in the first embodiment. During heat pressing, the rubber layer 51 adhered to the light-emitting elements 20 is penetrated by the first conductive electrode 22 and the second conductive electrode 23 of the light-emitting elements 20. Furthermore, the conductive particles 53 of the anisotropic conductive adhesive layer 52 are sandwiched between the first conductive electrode 22 and the second conductive electrode 23 of the light-emitting elements 20 and the first electrode 32 and the second electrode 33 of the wiring substrate 30, and are cured by the adhesive of the anisotropic conductive adhesive layer 52, thereby forming an anisotropic conductive film.
[0086] According to the manufacturing method of the connection structure according to the second embodiment, by disposing a rubber layer on the electrode surface of the chip component and disposing a connection film composed of an adhesive layer on the electrode surface of the wiring substrate, the rubber layer and the connection film collide, thereby suppressing the occurrence of defects such as chip component displacement, deformation, damage, and detachment during the landing process. This enables the chip component to be transferred and arranged with high precision and high efficiency. During the connection process, the chip component penetrates the rubber layer, resulting in excellent conductivity.
[0087] [Third Implementation Method]
[0088] In the first embodiment, a connecting film having a rubber layer and an adhesive layer is disposed on a wiring substrate, but the connecting film may also be disposed on the electrode surface of a chip component.
[0089] That is, the manufacturing method of the connection structure in the third embodiment includes: a landing step in which a chip component disposed on a substrate material that is permeable to laser is placed opposite a wiring substrate, and a laser is irradiated from the substrate material side to cause the chip component to land on the wiring substrate side; and a connection step in which the chip component and the wiring substrate are connected via a connection film, the connection film having a rubber layer and an adhesive layer, wherein in the landing step, the connection film is disposed on the electrode surface of the chip component, and the rubber layer collides with the electrode surface of the wiring substrate.
[0090] Hereinafter, similar to the first embodiment, the method for manufacturing a display device in which multiple light-emitting elements, which are LED chips, are arranged on a wiring substrate, which is a panel substrate, to form a light-emitting element array, will be described as a method for manufacturing a connecting structure. Furthermore, structures identical to those in the first embodiment will be labeled with the same reference numerals and their descriptions will be omitted.
[0091] [Landing process (A3)]
[0092] Figure 6 This is a schematic cross-sectional view showing a light-emitting element, which is disposed on a substrate material and has a connecting thin film on the electrode surface, facing a wiring substrate. For example... Figure 6As shown, firstly, in the placement process (A2), the chip component substrate 10 is positioned opposite the wiring substrate 30.
[0093] The chip component substrate 10 includes a substrate material 11, a release material 12, and a light-emitting element 20, with the light-emitting element 20 attached to the surface of the release material 12. Additionally, a connecting film 60 is attached to the electrode surface of the light-emitting element 20.
[0094] The connecting film 60 has a rubber layer 61 and an anisotropic conductive adhesive layer 62, with the rubber layer 61 side facing the wiring substrate 30. The rubber layer 61 and the anisotropic conductive adhesive layer 62 are the same as the rubber layer 41 and the anisotropic conductive adhesive layer 42 in the first embodiment, so the description is omitted.
[0095] In the landing process (A3), the rubber layer 61 on which the light-emitting element 20 is attached mitigates the impact when the light-emitting element 20, which is ejected at ultra-high speed, lands on the electrode surface of the wiring board 30, suppressing the occurrence of defects such as displacement, deformation, damage, and detachment of the light-emitting element 20, and thus achieving a high landing success rate.
[0096] [Connection process (B3)]
[0097] In the connection process (B3), the arranged light-emitting elements 20 are installed at predetermined positions on the wiring substrate 30. The method of heat-pressing the light-emitting elements 20 onto the wiring substrate 30 is the same as in the first embodiment. During heat pressing, the rubber layer 61 adhered to the light-emitting elements 20 is penetrated by the conductive particles 63 of the anisotropic conductive adhesive layer 62. Furthermore, the conductive particles 63 of the anisotropic conductive adhesive layer 62 are sandwiched between the first conductive electrode 22 and the second conductive electrode 23 of the light-emitting elements 20 and the first electrode 32 and the second electrode 33 of the wiring substrate 30, and are cured by the adhesive of the anisotropic conductive adhesive layer 62, thereby forming an anisotropic conductive film.
[0098] According to the manufacturing method of the connection structure according to the third embodiment, by disposing a connection film having a rubber layer and an adhesive layer on the electrode surface of the chip component, and causing the rubber layer to collide with the electrode surface of the wiring substrate, the occurrence of defects such as chip component displacement, deformation, damage, and detachment is suppressed in the landing process, enabling the chip component to be transferred and arranged with high precision and high efficiency, and excellent conductivity can be obtained in the connection process.
[0099] [Fourth Implementation Method]
[0100] In the first embodiment, a connecting film having a rubber layer and an adhesive layer is disposed on a wiring substrate, but the adhesive layer may also be disposed on the electrode surface of the chip component, and the rubber layer may be disposed on the wiring substrate.
[0101] That is, the manufacturing method of the connection structure in the fourth embodiment includes: a landing step in which a chip component disposed on a substrate material that is permeable to laser light is placed opposite a wiring substrate, and a laser light is irradiated from the substrate material side to cause the chip component to land on the wiring substrate side; and a connection step in which the chip component and the wiring substrate are connected via a connection film, the connection film having an adhesive layer, the wiring substrate having a rubber layer on the electrode surface, and in the landing step, the connection film is disposed on the electrode surface of the chip component, and the adhesive layer collides with the rubber layer of the wiring substrate.
[0102] Hereinafter, similar to the first embodiment, the method for manufacturing a display device in which multiple light-emitting elements, which are LED chips, are arranged on a wiring substrate, which is a panel substrate, to form a light-emitting element array, will be described as a method for manufacturing a connection structure. Furthermore, structures identical to those in the first embodiment will be labeled with the same reference numerals and their descriptions will be omitted.
[0103] [Landing process (A4)]
[0104] Figure 7 This is a schematic cross-sectional view showing a light-emitting element, which is disposed on a substrate material and has an anisotropic conductive adhesive layer on the electrode surface, facing a rubber layer on a wiring substrate. For example... Figure 7 As shown, firstly, in the placement process (A4), the chip component substrate 10 is positioned opposite the wiring substrate 30.
[0105] The chip component substrate 10 includes a substrate material 11, a release material 12, and a light-emitting element 20, with the light-emitting element 20 attached to the surface of the release material 12. Furthermore, a connecting film 70 composed of an anisotropic conductive adhesive layer 72 is attached to the electrode surface of the light-emitting element 20. The anisotropic conductive adhesive layer 72 is the same as the anisotropic conductive adhesive layer 42 in the first embodiment, and therefore its description is omitted.
[0106] Additionally, a rubber layer 71 is attached to the first electrode 32 and the second electrode 33 of the wiring board 30. The rubber layer 71 is the same as the rubber layer 41 in the first embodiment, so its description is omitted.
[0107] In the landing process (A4), the rubber layer 71 attached to the wiring board 30 mitigates the impact of the light-emitting element 20 when it lands at ultra-high speed, suppressing the occurrence of defects such as displacement, deformation, damage, and detachment of the light-emitting element 20, and thus achieving a high landing success rate.
[0108] [Connection process (B4)]
[0109] In the connection process (B4), the arranged light-emitting elements 20 are installed at predetermined positions on the wiring substrate 30. The method of heat-pressing the light-emitting elements 20 onto the wiring substrate 30 is the same as in the first embodiment. During heat pressing, the rubber layer 71 adhered to the wiring substrate 30 is penetrated by the conductive particles 73 of the anisotropic conductive adhesive layer 72. Furthermore, the conductive particles 73 of the anisotropic conductive adhesive layer 72 are sandwiched between the first conductive electrode 22 and the second conductive electrode 23 of the light-emitting element 20 and the first electrode 32 and the second electrode 33 of the wiring substrate 30, and are cured by the adhesive of the anisotropic conductive adhesive layer 72, thereby forming an anisotropic conductive film.
[0110] According to the manufacturing method of the connection structure according to the fourth embodiment, by disposing a connection film composed of an adhesive layer on the electrode surface of the chip component, disposing a rubber layer on the electrode surface of the wiring substrate, and colliding the adhesive layer with the rubber layer, the generation of defects such as chip component displacement, deformation, damage, and detachment can be suppressed in the landing process, enabling the chip component to be transferred and arranged with high precision and high efficiency, and excellent conductivity can be obtained in the connection process.
[0111] <2. Connecting film>
[0112] The connecting film of this embodiment has a rubber layer and an adhesive layer, wherein the thickness of the rubber layer is 0.5 μm or more and 3.0 μm or less. This improves the landing rate when, for example, laser-based mass transfer is used to place chip components onto a wiring substrate, resulting in excellent conductivity.
[0113] The adhesive layer is preferably an anisotropic conductive adhesive layer containing conductive particles. This allows the chip component to be connected to the wiring substrate even when no solder bumps or other connection points are provided on the chip component. Furthermore, the anisotropic conductive adhesive layer is preferably configured such that the conductive particles are arranged in the planar direction, and preferably biased towards the wiring substrate side in the thickness direction. This improves the trapping ability of conductive particles between the electrodes of the chip component and the electrodes of the wiring substrate. Moreover, even if the electrodes of the chip component are protruding or the like, and electrical connection with the wiring substrate is achieved, the adhesive layer may not contain conductive particles.
[0114] Figure 8 This is a schematic cross-sectional view illustrating a first example of the structure of the connecting film. (e.g.) Figure 8 As shown, the connecting film 40 has a rubber layer 41 and an anisotropic conductive adhesive layer 42 containing conductive particles 43.
[0115] The rubber layer 41 is not particularly limited to any elastomer with high cushioning (impact absorption) properties. Specific examples include silicone rubber, acrylic rubber, butadiene rubber, and polyurethane resin (polyurethane-based elastomer). Preferably, the rubber layer 41 is selected from one or more of silicone rubber and acrylic rubber.
[0116] The thickness of the rubber layer 41 is preferably 0.5 μm or more and 3.0 μm or less, more preferably 0.5 μm or more and 2.0 μm or less, and even more preferably 0.5 μm or more and 1.5 μm or less. If the thickness of the rubber layer 41 is too small, it tends to be difficult to obtain shock absorption, and if the thickness of the rubber layer 41 is too small, it tends to be difficult to obtain conductivity.
[0117] The hardness of the rubber layer 41 measured by the hardness tester A is preferably 20 to 40, more preferably 20 to 35, and even more preferably 20 to 30. If the hardness of the hardness tester A is too high, the rubber layer becomes too hard, which may cause deformation or damage to the chip components. If the hardness of the hardness tester A is too low, the rubber layer 41 becomes too soft, which may cause misalignment of the chip components. The hardness of the rubber layer 41 can be measured using the hardness tester A based on JIS K6253, using the rubber hardness (Japanese Industrial Standard JIS-A hardness).
[0118] The storage modulus of the rubber layer 41 at a temperature of 30°C and a frequency of 200Hz, as determined by the dynamic viscoelasticity test using a push-in test apparatus, is preferably 60 MPa or less, more preferably 40 MPa or less, and even more preferably 30 MPa or less. If the storage modulus is too high at 30°C and 200Hz, it cannot absorb the impact of the chip component ejected at high speed by laser irradiation, leading to a tendency for a decrease in the transfer rate of the chip component. The storage modulus of the rubber layer 41 at 30°C and 200Hz can be determined using a push-in test apparatus, for example, using a flat punch with a diameter of 100 μm, setting the target push-in depth to 1 μm, and a scanning frequency in the range of 1–200Hz.
[0119] The anisotropic conductive adhesive layer 42 can also be a so-called anisotropic conductive film (ACF) containing conductive particles 43. As the conductive particles, conductive particles known for use in anisotropic conductive films can be appropriately selected. Examples include metal particles such as nickel, copper, silver, gold, palladium, and solder, and metal-coated resin particles formed by coating the surface of resin particles such as polyamide and polybenzoguanamine with metals such as nickel and gold. Therefore, conductivity can be achieved even when the chip component does not have solder bumps or other connection points.
[0120] Furthermore, the anisotropic conductive adhesive layer 42 is preferably configured such that the conductive particles 43 are arranged in the planar direction. By arranging the conductive particles in the planar direction, the particle surface density becomes uniform, resulting in excellent conductivity. Additionally, the anisotropic conductive adhesive layer 42 preferably has the conductive particles 43 biased towards the wiring substrate side in the thickness direction. For example, in the first embodiment described above, the conductive particles 43 in the anisotropic conductive adhesive layer 42 may be biased towards the side opposite to the surface of the rubber layer 41; similarly, in the third embodiment described above, the conductive particles 43 in the anisotropic conductive adhesive layer 42 may be biased towards the surface of the rubber layer 41. This improves the trapping ability of conductive particles between the electrodes of the chip component and the electrodes of the wiring substrate.
[0121] The particle size of the conductive particles 43 is not particularly limited, but the lower limit of the particle size is preferably 1 μm or more, and the upper limit of the particle size, for example, from the viewpoint of the capture efficiency of conductive particles in the connecting structure, is preferably 50 μm or less, and more preferably 20 μm or less. Furthermore, the particle size of the conductive particles can be set to a value measured by an image-type particle size analyzer (for example, FPIA-3000: manufactured by Malvern). This number is preferably 1000 or more, and more preferably 2000 or more. Additionally, the particle surface density of the conductive particles can be determined according to the electrode area of the chip components, and for example, can be set to 500 to 140,000 pcs / mm². 2 The range.
[0122] The anisotropic conductive adhesive layer 42 is preferably composed of a thermosetting adhesive containing a film-forming resin, a thermosetting resin, and a curing agent. The thermosetting adhesive is not particularly limited; examples include thermosetting anionic polymeric resin compositions containing an epoxy compound and a thermosetting anionic polymerization initiator, thermosetting cationic polymeric resin compositions containing an epoxy compound and a thermosetting cationic polymerization initiator, and thermosetting free radical polymeric resin compositions containing a (meth)acrylate compound and a thermosetting free radical polymerization initiator. Furthermore, the term "(meth)acrylate compound" refers to a composition containing both acrylic acid monomers (oligomers) and methacrylic acid monomers (oligomers).
[0123] In the aforementioned thermosetting adhesives, it is preferable that the thermosetting resin contains an epoxy compound and the curing agent is a thermosetting cationic polymerization initiator. This suppresses the laser-induced curing reaction and allows for rapid curing using heat. Hereinafter, as a specific example, a thermosetting cationic polymeric resin composition containing a film-forming resin, an epoxy compound, and a thermosetting cationic polymerization initiator will be described.
[0124] As a film-forming resin, for example, a high molecular weight resin with an average molecular weight of 10,000 or more is preferred, from the viewpoint of film formation properties, having an average molecular weight of around 10,000 to 80,000. Examples of film-forming resins include phenoxy resins, polyester resins, polyurethane resins, polyester-polyurethane resins, acrylic resins, polyimide resins, and butyral resins; these resins can be used alone or in combination of two or more. From the viewpoint of film formation state and bonding reliability, phenoxy resin is preferred. The content of the film-forming resin in the anisotropic conductive adhesive layer is preferably 20 to 50 wt%, more preferably 25 to 45 wt%, and even more preferably 30 to 40 wt%.
[0125] The epoxy compound is not particularly limited as long as it has one or more epoxy groups within its molecule. Examples include bisphenol A type epoxy resin, bisphenol F type epoxy resin, and urethane-modified epoxy resin. High-purity bisphenol A type epoxy resin is preferred. A specific example of high-purity bisphenol A type epoxy resin is the trade name "YL980" manufactured by Mitsubishi Chemical Co., Ltd. The content of the epoxy compound in the anisotropic conductive adhesive layer is preferably 10–55 wt%, more preferably 15–50 wt%, and even more preferably 20–45 wt%.
[0126] As a thermo-cationic polymerization initiator, a known thermo-cationic polymerization initiator can be used as the thermo-cationic polymerization initiator for epoxy compounds. For example, an acid that can be generated by heat to cationically polymerize cationic polymeric compounds can be used, such as known iodonium salts, sulfonium salts, phosphonium salts, ferrocene, etc. Among these, aromatic sulfonium salts with good temperature characteristics are preferred. Specific examples of aromatic sulfonium salt polymerization initiators include, for example, the trade name "SI-60L" manufactured by Sanshin Chemical Industry Co., Ltd. The content of the thermo-cationic polymerization initiator in the anisotropic conductive adhesive layer is preferably 1 to 20 wt%, more preferably 2 to 15 wt%, and even more preferably 3 to 12 wt%.
[0127] In addition, as other additives that can be used with thermosetting adhesives, inorganic fillers, silane coupling agents, diluent monomers, fillers, softeners, colorants, flame retardants, thixotropic agents, etc., can also be added as needed.
[0128] Silicon, talc, titanium dioxide, calcium carbonate, magnesium oxide, etc., can be used as inorganic fillers. Inorganic fillers can be used alone or in combination with two or more. The content of inorganic fillers in the anisotropic conductive adhesive layer is preferably 1–30 wt%, more preferably 5–25 wt%, and even more preferably 10–20 wt%. When two or more inorganic fillers are used simultaneously, the total content of inorganic fillers in the thermosetting adhesive is preferably within the above-mentioned range.
[0129] The lower limit of the thickness of the anisotropic conductive adhesive layer 42 can be, for example, the same as the particle diameter of the conductive particles, and preferably can be set to 1.3 times or more the particle diameter of the conductive particles or 3 μm or more. Furthermore, the upper limit of the thickness of the connecting film can be, for example, 20 μm or less or 2 times or less the particle diameter of the conductive particles. Additionally, the connecting film can also be formed by laminating adhesive layers and adhesive layers that do not contain conductive particles; the number of layers and the lamination surfaces can be appropriately selected according to the object and purpose. Furthermore, the insulating resin used as the adhesive layer and adhesive layer can be the same insulating resin as that used in the connecting film. The film thickness can be measured using a known micrometer or digital thickness gauge. For example, the film thickness can be calculated by averaging measurements taken at 10 or more locations.
[0130] [Variation Example]
[0131] In the first embodiment, the rubber layer preferably has internal voids, and is preferably in a mesh-like or protruding shape. This allows for improved shock absorption through the air layer, increasing the chip component's landing rate. Furthermore, during chip component connection, the chip component easily penetrates the rubber layer, thus achieving excellent on-resistance.
[0132] Figure 9 (A) is a top view showing two rubber layers with internal gaps created through processing. Figure 9 (B) is a schematic cross-sectional view illustrating a second example of the connecting film. Figure 9 As shown, the connecting film 80, as a second configuration example, has a rubber layer 81 and an anisotropic conductive adhesive layer 82 containing conductive particles 83. The rubber layer 81 is formed by stacking a first rubber layer 81A and a second rubber layer 81B, and is, for example, formed in a mesh shape (sieve type). The first rubber layer 81A and the second rubber layer 81B are cured by using a plurality of convex molds, thereby forming a plurality of pores on their surfaces. Alternatively, the rubber layer 81 may not be a sieve type, but rather a porous layer. Furthermore, the anisotropic conductive adhesive layer 82 is the same as the anisotropic conductive adhesive layer 42, and therefore its description is omitted.
[0133] Figure 10 This is a schematic cross-sectional view illustrating a third example of the connecting film. (e.g.) Figure 10As shown, the connecting film 90, as a third configuration example, has a rubber layer 91 and an anisotropic conductive adhesive layer 92 containing conductive particles 93. The rubber layer 91 is, for example, a protruding shape (protrusion type), and multiple holes are formed on the surface by curing the rubber using a plurality of convex molds. Furthermore, the anisotropic conductive adhesive layer 92 is the same as the anisotropic conductive adhesive layer 42, so its description is omitted.
[0134] As in the modified example, the internal voids in the rubber layer improve shock absorption and increase the chip component placement rate. Furthermore, the permeability of the rubber layer is improved, resulting in excellent on-resistance.
[0135] Example
[0136] <3. Example>
[0137] In one embodiment, a chip component disposed on quartz glass was positioned opposite a connecting film disposed on a glass substrate, and a laser was irradiated from the substrate material side to cause the chip component to land on the connecting film. The landing performance was then evaluated. Furthermore, a connecting structure was fabricated, and its conductivity was evaluated. However, this technology is not limited to these embodiments.
[0138] Fabrication of anisotropic conductive adhesive layer
[0139] The following materials have been prepared.
[0140] Phenoxy resin (trade name: PKHH, manufactured by Pakistan Chemical Industry Co., Ltd.)
[0141] High-purity bisphenol A type epoxy resin (trade name: YL-980, manufactured by Mitsubishi Chemical Co., Ltd.)
[0142] Hydrophobic silicon (trade name: RY200, manufactured by Aerosil Corporation of Japan)
[0143] Cationic polymerization initiator (trade name: SI-60L, manufactured by Sanxin Chemical Industry Co., Ltd.)
[0144] Conductive particles (average particle size 3μm, resin core metal-coated microparticles, Ni plating thickness 0.2μm, manufactured by Sekisui Chemicals Co., Ltd.)
[0145] As shown in Table 2, by combining the various materials with predetermined mass fractions, an anisotropic conductive adhesive layer with a thickness of 6 μm was fabricated on a glass substrate with a thickness of 0.5 mm. The anisotropic conductive adhesive layer, for example, is fabricated according to the method described in Patent No. 6187665, with the conductive particles having a particle surface density of 58000 pcs / mm². 2 They are arranged in a manner on one side of the adhesive layer.
[0146] [Table 2]
[0147] Material Coordination Department (Quality Department) phenoxy resin 35 High-purity bisphenol A type epoxy resin 40 Hydrophobic silicon 15 cationic polymerization initiator 10
[0148] [Evaluation of chip component placement]
[0149] A listing device (MT-30C200) is used to place a chip component mounted on quartz glass onto a bonding film on a glass substrate. The chip component (30×50μm in size, 5μm in thickness, and 2μm in electrode thickness) uses a TEG (Test Element Group), and a release material (polyimide) is provided between the quartz glass and the chip component.
[0150] As described above, the listing device includes: a telescoping member that makes the pulsed laser emitted from the laser device parallel light; a shaping optical system that uniformly shapes the spatial intensity distribution of the pulsed laser after passing through the telescoping member; a mask that allows the pulsed laser shaped by the shaping optical system to pass through in a predetermined pattern; a field lens located between the shaping optical system and the mask; and a projection lens that projects the laser pattern after passing through the mask onto a donor substrate in a reduced manner. A quartz substrate, which serves as the donor substrate and holds the chip component with a release material, is held on a donor stage, and a glass substrate, which serves as the recipient substrate and has a connecting film attached to it, is held on a recipient stage. The distance between the chip component and the connecting film is set to 100 μm.
[0151] The laser device used an excimer laser with an oscillation wavelength set to 248 nm. The laser pulse energy was 600 J, and the flux was 150 J / cm³. 2 The pulse width (irradiation time) is 30,000 picoseconds, the pulse frequency is 0.01 kHz, and the number of pulses for irradiating a small area of each ACF is 1 pulse. The pulse energy of the imaging laser irradiating the interface between the anisotropic conductive adhesive layer and the substrate material is 0.001–2 J, and the flux is 0.001–2 J / cm³. 2 The pulse width (irradiation time) is 0.01 to 1×10⁻⁶. 9 The pulse frequency is 0.1–10000 Hz, and the number of irradiation pulses is 1–30,000,000.
[0152] The mask uses a pattern of windows of a predetermined size arranged at a predetermined spacing, so that the projection in the boundary between the quartz glass, which serves as the donor substrate, and the release material becomes the outline of the chip component, which is 30×50μm.
[0153] A total of 100 chip components are transferred to a bonding film, and the number of chip components that are normally deposited on the bonding film is counted using a microscope. The proportion of normally deposited chip components is preferably above 90%.
[0154] [Creating a Connector]
[0155] The chip component was placed onto the connection film of the wiring substrate and thermo-bonded under conditions of 170°C, 10 MPa, and 30 seconds to create the connection structure. The chip component (50 μm × 50 μm in shape, 150 μm in thickness) used a TEG (Test Element Group) with a pair of electrodes (Cr / Au-plated bump 12 μm × 12 μm) on it. The wiring substrate used a glass substrate (0.5 mm thick, Ti / Al / Ti pattern 12 μm × 12 μm).
[0156] [Evaluation of Conductivity]
[0157] The on-resistance of the connection structure was measured using the conductive wiring on the wiring board side. Conductivity was evaluated based on the resistance value, and judgments were made from A to D below. A judgment of C or higher is preferred.
[0158] A: Below 50Ω
[0159] B: 50Ω or more but less than 100Ω
[0160] C: More than 100Ω but less than 200Ω
[0161] D: Over 200Ω
[0162] [Example 1]
[0163] After coating with silicone (trade name: STP-106T-UV, manufactured by Shin-Etsu Chemical Co., Ltd.), a 1μm thick silicone rubber layer was produced by UV (ultraviolet) curing. Furthermore, the 1μm thick silicone rubber layer was bonded to the surface of a 6μm thick anisotropic conductive adhesive layer to form a bonding film.
[0164] In addition, regarding silicone rubber, the hardness (Japanese Industrial Standard JIS-A hardness) was measured using a durometer A based on JIS K6253. The result showed a hardness of 30. Furthermore, regarding silicone rubber, dynamic viscoelasticity tests were conducted using an indentation testing apparatus (KLA iMicro nanoindenter). Using a 100 μm diameter flat punch, the target indentation depth was set to 1 μm, and the scanning frequency range was 1–200 Hz. The storage modulus was measured at a temperature of 30°C and a frequency of 200 Hz. The Poisson's ratio of the samples was set to 0.5, and the average value of the 12 measurement points for each sample was calculated. The result showed a storage modulus of 27 MPa.
[0165] As shown in Table 3, the chip landing rate when the chip component lands on the silicone rubber layer of the bonding film is 98%. In addition, the on-resistance of the connection structure obtained by thermally bonding the chip component to the wiring substrate via the bonding film is evaluated as "B".
[0166] [Example 2]
[0167] In addition to fabricating a silicone rubber layer with a thickness of 0.5 μm, a connecting film was also fabricated in the same manner as in Example 1.
[0168] As shown in Table 3, the chip landing rate when the chip component lands on the silicone rubber layer of the bonding film is 90%. In addition, the on-resistance of the connection structure obtained by thermally bonding the chip component to the wiring substrate via the bonding film is evaluated as "A".
[0169] [Example 3]
[0170] In addition to fabricating a silicone rubber layer with a thickness of 2.0 μm, a connecting film was also fabricated in the same manner as in Example 1.
[0171] As shown in Table 3, the chip landing rate is 100% when the chip component lands on the silicone rubber layer of the connecting film. In addition, the on-resistance of the connection structure obtained by thermally bonding the chip component to the wiring substrate via the connecting film is evaluated as "C".
[0172] [Example 4]
[0173] After coating a 1μm thick layer of silicone (trade name: STP-106T-UV, manufactured by Shin-Etsu Chemical Co., Ltd.), multiple 1μm diameter holes were created using a convex embossing process, followed by UV (ultraviolet) curing to produce a silicone rubber layer. Then, two silicone rubber layers, with a combined thickness of 2μm, were aligned and bonded (using a mesh-like method) onto the surface of a 6μm thick anisotropic conductive adhesive layer to form a bonding film.
[0174] As shown in Table 3, the chip landing rate is 100% when the chip component lands on the silicone rubber layer of the connecting film. In addition, the on-resistance of the connection structure obtained by thermally bonding the chip component to the wiring substrate via the connecting film is evaluated as "A".
[0175] [Example 5]
[0176] After applying a silicone coating of a predetermined thickness (trade name: STP-106T-UV, manufactured by Shin-Etsu Chemical Co., Ltd.), multiple 1μm diameter holes were embossed using a raised pattern, followed by UV (ultraviolet) curing to create a silicone rubber layer with a protrusion height of 1μm or more and a total thickness of 2μm. Furthermore, the silicone rubber layer (protrusion type) was bonded to the surface of a 6μm thick anisotropic conductive adhesive layer to form a bonding film.
[0177] As shown in Table 3, the chip landing rate is 100% when the chip component lands on the silicone rubber layer of the connecting film. In addition, the on-resistance of the connection structure obtained by thermally bonding the chip component to the wiring substrate via the connecting film is evaluated as "A".
[0178] [Comparative Example 1]
[0179] The silicone rubber layer is not bonded to the surface of the anisotropic conductive adhesive layer; instead, the 6μm thick anisotropic conductive adhesive layer is used as the connecting film.
[0180] As shown in Table 3, the chip placement rate when the chip component is placed on the anisotropic conductive adhesive layer is 20%. In addition, the on-resistance of the connection structure obtained by thermally bonding the chip component to the wiring substrate via the connecting film is evaluated as "A".
[0181] [Comparative Example 2]
[0182] Compared to 80 parts of silicon (trade name: STP-106T-UV, manufactured by Shin-Etsu Chemical Co., Ltd.), 20 parts of conductive particles (average particle size 3μm, resin core metal-coated microparticles, Ni-plated 0.2μm thick, manufactured by Sekisui Chemical Co., Ltd.) were coated onto a 0.5mm thick glass substrate and UV cured to create a 6μm thick silicone rubber layer containing conductive particles, which was then used as a bonding film.
[0183] As shown in Table 3, the chip landing rate is 100% when the chip component is placed on the silicone rubber layer containing conductive particles. In addition, the on-resistance of the connection structure obtained by thermally bonding the chip component to the wiring substrate via the connection film is evaluated as "D".
[0184] [Table 3]
[0185]
[0186] As shown in Table 3, in Comparative Example 1, the chip landing rate was low because a silicone rubber layer was not provided on the anisotropic conductive adhesive layer. In Comparative Example 2, the on-resistance was poorly evaluated because the bonding film was a silicone rubber layer containing conductive particles.
[0187] On the other hand, in Examples 1-5, since a silicone rubber layer is provided on the anisotropic conductive adhesive layer, a high chip landing rate can be obtained. Furthermore, in Examples 4 and 5, since the silicone rubber layer is of the mesh type, protrusion type, or similar type with internal voids, the chip components can easily penetrate the silicone rubber layer, resulting in a good evaluation of on-resistance.
[0188] Symbol Explanation
[0189] 10—Chip component substrate, 11—Base material, 12—Release material, 20—Light-emitting element, 21—Main body, 22—First conductive electrode, 23—Second conductive electrode, 30—Wiring substrate, 31—Base material, 32—First electrode, 33—Second electrode, 40—Connecting film, 41—Rubber layer, 42—Anisotropic conductive adhesive layer, 50—Connecting film, 51—Rubber layer, 52—Anisotropic conductive adhesive layer, 60—Connecting film, 61—Rubber layer, 62—Anisotropic conductive adhesive layer, 70—Connecting film 71—Rubber layer, 72—Anisotropic conductive adhesive layer, 80—Connecting film, 81—Rubber layer, 82—Anisotropic conductive adhesive layer, 83—Conductive particles, 90—Connecting film, 91—Rubber layer, 92—Anisotropic conductive adhesive layer, 93—Conductive particles, 101—LED, 102—Transfer material, 103—Imprint material, 104—Panel substrate, 105—Connecting film, 111—LED, 112—Transfer material, 113—Release material, 114—Panel substrate, 115—Connecting film.
Claims
1. A method for manufacturing a connecting structure, characterized in that, have: The placement process involves placing a chip component disposed on a substrate material that is permeable to laser light onto a wiring substrate, and irradiating the chip component onto the wiring substrate side by irradiating it with laser light from the substrate material side; and The connection process connects the aforementioned chip components to the aforementioned wiring substrate via a connection film. The aforementioned connecting film has a rubber layer and an adhesive layer. In the aforementioned landing process, the aforementioned connecting film is disposed on the electrode surface of the aforementioned wiring substrate, causing the aforementioned rubber layer to collide with the electrode surface of the aforementioned chip component. The hardness of the rubber layer is 20 to 40 according to the hardness tester A, and the energy storage modulus is less than 60 MPa at a temperature of 30°C and a frequency of 200 Hz in the dynamic viscoelastic test using the push-in test device.
2. A method for manufacturing a connecting structure, characterized in that, have: The landing process involves placing a chip component disposed on a substrate material that is permeable to laser light onto a wiring substrate, and irradiating the chip component onto the wiring substrate side by irradiating the substrate material side with laser light. as well as The connection process connects the aforementioned chip components to the aforementioned wiring substrate via a connection film. The aforementioned connecting film has an adhesive layer. The aforementioned chip component has a rubber layer on the electrode surface. In the above-mentioned landing process, the above-mentioned connecting film is disposed on the electrode surface of the above-mentioned wiring substrate, so that the above-mentioned adhesive layer collides with the rubber layer of the above-mentioned chip component. The hardness of the rubber layer is 20 to 40 according to the hardness tester A, and the energy storage modulus is less than 60 MPa at a temperature of 30°C and a frequency of 200 Hz in the dynamic viscoelastic test using the push-in test device.
3. A method for manufacturing a connecting structure, characterized in that, have: The placement process involves placing a chip component disposed on a substrate material that is permeable to laser light onto a wiring substrate, and irradiating the chip component onto the wiring substrate side by irradiating it with laser light from the substrate material side; and The connection process connects the aforementioned chip components to the aforementioned wiring substrate via a connection film. The aforementioned connecting film has a rubber layer and an adhesive layer. In the aforementioned landing process, the aforementioned connecting film is disposed on the electrode surface of the aforementioned chip component, causing the aforementioned rubber layer to collide with the electrode surface of the aforementioned wiring substrate. The hardness of the rubber layer is 20 to 40 according to the hardness tester A, and the energy storage modulus is less than 60 MPa at a temperature of 30°C and a frequency of 200 Hz in the dynamic viscoelastic test using the push-in test device.
4. A method for manufacturing a connecting structure, characterized in that, have: The placement process involves placing a chip component disposed on a substrate material that is permeable to laser light onto a wiring substrate, and irradiating the chip component onto the wiring substrate side by irradiating it with laser light from the substrate material side; and The connection process connects the aforementioned chip components to the aforementioned wiring substrate via a connection film. The aforementioned connecting film has an adhesive layer. The aforementioned wiring substrate has a rubber layer on the electrode surface. In the above-mentioned landing process, the above-mentioned connecting film is disposed on the electrode surface of the above-mentioned chip component, so that the above-mentioned adhesive layer collides with the rubber layer of the above-mentioned wiring substrate. The hardness of the rubber layer is 20 to 40 according to the hardness tester A, and the energy storage modulus is less than 60 MPa at a temperature of 30°C and a frequency of 200 Hz in the dynamic viscoelastic test using the push-in test device.
5. The method for manufacturing the connecting structure according to any one of claims 1 to 4, characterized in that, The aforementioned rubber layer is selected from one or more types of acrylic rubber and silicone rubber.
6. The method for manufacturing a connecting structure according to any one of claims 1 to 4, characterized in that, The thickness of the aforementioned rubber layer is 0.5 μm or more and 3.0 μm or less.
7. The method for manufacturing a connecting structure according to any one of claims 1 to 4, characterized in that, The aforementioned rubber layer has internal voids.
8. The method for manufacturing a connecting structure according to any one of claims 1 to 4, characterized in that, The adhesive layer described above contains a film-forming resin, a thermosetting resin, and a curing agent.
9. The method for manufacturing a connecting structure according to any one of claims 1 to 4, characterized in that, The adhesive layer described above contains conductive particles.
10. The method for manufacturing a connecting structure according to claim 9, characterized in that, The aforementioned adhesive layer is formed by arranging the aforementioned conductive particles in the planar direction.
11. The method for manufacturing a connecting structure according to any one of claims 1 to 4, characterized in that, The aforementioned chip component is a light-emitting element.
12. A connecting film, characterized in that, It has a rubber layer and an adhesive layer. The thickness of the aforementioned rubber layer is 0.5 μm or more and 3.0 μm or less. The hardness of the rubber layer is 20 to 40 according to the hardness tester A, and the energy storage modulus is less than 60 MPa at a temperature of 30°C and a frequency of 200 Hz in the dynamic viscoelastic test using the push-in test device.
13. The connecting film according to claim 12, characterized in that, The aforementioned rubber layer is selected from one or more types of acrylic rubber and silicone rubber.
14. The connecting film according to claim 12 or 13, characterized in that, The aforementioned rubber layer has internal voids.
15. The connecting film according to claim 12 or 13, characterized in that, The adhesive layer described above contains a film-forming resin, a thermosetting resin, and a curing agent.
16. The connecting film according to claim 12 or 13, characterized in that, The adhesive layer described above contains conductive particles.
17. The connecting film according to claim 16, characterized in that, The aforementioned adhesive layer is formed by arranging the aforementioned conductive particles in the planar direction.
Citation Information
Patent Citations
Transfer method, method of manufacturing image display device using the same, and transfer device
JP2020053558A
Element array manufacturing method and specific element removing method
JP2020096144A
Chip transfer plate, chip transfer method, image display device manufacturing method, and semiconductor device manufacturing method
JP2020145243A
Ventilation system
JP2021081171A
Cushioning material for hot pressing
JP2013132889A
